Phenotype and genotype variation, stem cutting growth performance and pod maturity of Moringa oleifera - Mohamad, Munirah (2013)
Moringa oleifera is a multipurpose tree as it is cultivated for vegetable, spice, cosmestic oil and medicinal plant. M. oleifera oil contains all the main fatty acid including oleic acid which is very stable when used for frying. Moreover, it has the potential to become a new source of high oleic acid oil. Previous study only focused on medicinal and nutritional aspects of the tree parts. However, there is lack of information on the morphological and genetic variations of M. oleifera grown in Malaysia. Thus, the objectives of the study were to determine the phenotypic and genotypic variations among M. oleifera accessions, the performance of stem cuttings of two selected accessions as propagation material, and the growth and maturation of pod of a selected accession. Morphological characteristics and ISSR molecular markers were used to assess levels of polymorphism across 20 accessions of M. oleifera in situ and ex situ. There were variations on morphological characteristics between accessions of M. oleifera based on stem girth, leaf length, leaf width, pod length, pod diameter, pod weight, seed number/pod, seed diameter and seed weight indicating the presence of genetic variability among accessions. Among the 20 accessions S05 had the highest seed weight followed by S04, with a difference of 3.7% seed weight. As for seed number/pod, accession P05 had the highest value followed by P03, with a difference of 4.7%. These two characteristics are beneficial in the selection of M. oleifera as they contribute to the total yield. The molecular analysis by using ISSR showed high polymorphism and abundance of ISSR sequences in M. oleifera. There were six cluster in the dendrogram with the majority of accessions from Perak and Selangor states being clustered separately. In the experiment on the performance of stem cuttings, two accessions (S05 and P05) were selected as propagation materials based on the highest seed weight (S05) and seed number/pod (P05). Six types of cuttings, fresh and dried hardwood, fresh and dried semi-hardwood and fresh and dried softwood were evaluated as the most suitable as planting materials. M. oleifera could be propagated successfully by using fresh semihardwood cutting compared to the other five types of cuttings. Cuttings from fresh semihardwood had better shoot and adventitious root production, thus had a good overall growth performance. For the determination of pod growth and maturation, accession S05 was selected to be grown in the field plot. In this experiment, pod and seed characteristics were determined 5-9 days after anthesis (DAA). Pod size increased gradually at 9 DAA, followed by a rapid increment at 9-37 DAA. Pods were observed to be at edible stage at 35-37 DAA. Pod size increased slowly between 37 to 44 DAA as pods were observed to become fully matured (oil extraction stage). Then, the increase in pod size levelled off at 44 DAA. Colour of edible pods and fully matured pods were observed to be light green and brown, respectively. Morphological characteristics and ISSR molecular markers showed high polymorphism and grouped to the accessions in six clusters. Subsequently, for selection of propagation materials, cuttings for fresh semi-hardwood showed optimum growth performance compared to other materials. For growth and development of seeds and pods, full maturity was achived at 44 DAA. These findings could be used as background information for breeding and improvement program of M. oleifera in Malaysia.